MENINGKATAKAN KEMAMPUAN OPERASI HITUNG BILANGAN DESIMAL MENGGUNAKAN METODE DRILL PADA SISWA KELAS V SD - Adam, Rahman Andika Apriyanto K.; Husain, Rusmin I; Aries, Nur Sakinah; Marshanawiah, Andi; Kudus, Kudus (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
This study aimed to improve fifth-grade students’ ability in performing decimal number operations at SDN 2 Telaga, Telaga District, Gorontalo Regency. The ability to perform decimal operations is an essential competency in elementary mathematics learning; however, in practice, many students still experience difficulties in understanding and applying these concepts. This research employed a Classroom Action Research (CAR) design conducted in a gradual and continuous manner, involving 19 students as research participants. Data were collected through learning achievement tests to measure improvements in students’ decimal operation skills and observations to examine teacher and student activities during the learning process. The collected data were analyzed using descriptive quantitative and qualitative analysis techniques. The results indicated that the implementation of the drill method significantly improved students’ ability to perform decimal operations. Learning mastery increased from 63.2% in Cycle I to 89.5% in Cycle II, with the class average score reaching 82. In addition to improved learning outcomes, student learning activities also increased from a fair category to a very good category. Therefore, the drill method was proven to be effective in enhancing elementary school students’ decimal arithmetic skills. ABSTRAK Penelitian ini bertujuan untuk meningkatkan kemampuan operasi hitung bilangan desimal pada siswa kelas V SDN 2 Telaga, Kecamatan Telaga, Kabupaten Gorontalo. Kemampuan operasi hitung bilangan desimal merupakan salah satu kompetensi penting dalam pembelajaran matematika di sekolah dasar, namun dalam praktiknya masih banyak siswa yang mengalami kesulitan dalam memahami dan menerapkannya. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (PTK) yang dilaksanakan secara bertahap dan berkelanjutan, dengan subjek penelitian sebanyak 19 siswa. Teknik pengumpulan data meliputi tes hasil belajar untuk mengukur peningkatan kemampuan operasi hitung bilangan desimal siswa serta observasi untuk mengetahui aktivitas guru dan siswa selama proses pembelajaran. Data yang diperoleh dianalisis menggunakan teknik analisis deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa penerapan metode Drill mampu meningkatkan kemampuan operasi hitung bilangan desimal siswa secara signifikan. Ketuntasan belajar siswa mencapai 63,2% pada siklus I dan meningkat menjadi 89,5% pada siklus II, dengan rata-rata nilai kelas mencapai 82. Selain peningkatan hasil belajar, aktivitas siswa selama pembelajaran juga mengalami peningkatan, dari kategori cukup menjadi kategori sangat baik. Dengan demikian, metode Drill terbukti efektif dalam meningkatkan kemampuan berhitung bilangan desimal siswa sekolah dasar.